2013
DOI: 10.1002/iub.1205
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 receptor antagonist gene polymorphism and hepcidin in rheumatoid arthritis: Correlations with clinical and laboratory indices of disease activity

Abstract: Rheumatoid arthritis (RA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(31 reference statements)
1
6
1
1
Order By: Relevance
“…15 It is found that experimental hepcidin increase in humans, induced by IL-6 infusion, is accompanied by a decrease in serum iron levels. 20 Swellam et al 24 found that hepcidin is significantly correlated with laboratory anemia profile indicating that hepcidin binds to, and degrades ferroportin, thus reduces intestinal absorption of iron and blocks mobilization of iron from macrophages and hepatocytes, causing low serum iron and anemia through decreased iron reutilization.…”
Section: Discussionmentioning
confidence: 99%
“…15 It is found that experimental hepcidin increase in humans, induced by IL-6 infusion, is accompanied by a decrease in serum iron levels. 20 Swellam et al 24 found that hepcidin is significantly correlated with laboratory anemia profile indicating that hepcidin binds to, and degrades ferroportin, thus reduces intestinal absorption of iron and blocks mobilization of iron from macrophages and hepatocytes, causing low serum iron and anemia through decreased iron reutilization.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have consistently pointed out the role of IL-Ra gene polymorphism in the disease activity of RA. For instance, RA patients with persistent active disease, had significantly increased expression of IL-1RN*1 and IL-1RN*2 [ 25 ]. Apart from that, another study which involved Spanish RA patients also found a significant association between homozygosity for IL1RN*2 with increased number of affected joints [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer patients, the serum concentrations of Follistatin have been shown to significantly correlate with the presence of bone metastases (P = 0.0005) [29]. Five of the 29 proteins have been reported to be associated with orthopedic disease: 1) The hepcidin gene showed a significant correlation with the RA disease activity parameters [30]. 2) Thioredoxin was a biomarker for oxidative stress in patients with rheumatoid arthritis [31].…”
Section: Results Of Go Analysis Of the Differentially Proteinsmentioning
confidence: 99%